Impact of Domestic Tourist Spending on the Economy of West Java Province, Indonesia - Agustian Harahap; Isabella Fitria Andjanie; Baiq Rizky Fatmasari; Wiwik Dwi Pratiwi (ASEAN Journal on Hospitality and Tourism, 2023)
The development of tourism in West Java in recent years has shown an increasing trend in domestic tourists until 2021. The increased number of domestic tourists has had an impact on West Java's economic activity. However, the tourism sector itself is not defined as a distinct sector in economic statistics, and as a result, the economic impact from tourism contributions is not quite noticeable, especially in West Java Province. This study aims to highlight the impact of tourism on the economy of West Java by examining domestic tourist spending in 2021 and its effect on the economy. The study estimates the multiplier effect of domestic tourists' spending on production, income, gross value added, and employment, to determine the economic impact of tourism. The results of this study indicate that tourism has a significant impact and plays a significant role in the West Java economy, contributing 9.28% to GRDP and 12.39% of the total working population in West Java in 2021.